Application of Lean Manufacturing to Minimize Waste in the Lajiem Coffee Business Production Process - Farid Ridzal Faridzi (Indonesian Vocational Research Journal, 2023)
Background - This study aims to implement the Lean Manufacturing method in the production sector in order to minimize the existance of waste in production proses of Lajiem Coffee. Design/methodology/approach - This type of research is qualitative research. By using the Lean Manufacturing method, the waste in the production sector of Coffee can be identified. The analysis used in this research is interactive models. Research implication - The results of waste identification using Timwood waste in the production sector found are Defect and Motion. Next, look for the root cause using 5-Why's in Root Cause Analysis (RCA), then assessed through Risk Analysis and mapped in a risk assessment matrix to find out the root causes of extreme risk. It is known that the extreme risks in the production sector are defects and motion. The next extreme risk is given improvement suggestions in order to minimize and reduce waste that has occurred in the production.